Integral inequalities of the Hermite – Hadamard type for $K$ -bounded norm convex mappings - Dragomir, S. S. (Ukrains’kyi Matematychnyi Zhurnal, 2016)
We obtain some inequalities of the Hermite – Hadamard type for $K$-bounded norm convex mappings between two normedspaces. The applications for twice differentiable functions in Banach spaces and functions defined by power series inBanach algebras are presented. Some discrete Jensen-type inequalities are also obtained.